COMPARATIVE ANALYSIS OF THE ROLE OF MAIZE FARMING AND AGRICULTURAL MARKET REFORMS IN RAISING FARMERS’ INCOME IN INDIA - RAVI KUMAR*; PUSHPA M. SAVADATTI (The Journal of Research ANGRAU, 2023)
The study aimed to investigate the compound annual growth rate (CAGR) of area, production, and yield of rice, wheat, and maize in India from 1950-51 to 2019-20, divided into four periods based on the vital year of the Indian economy from an agricultural perspective. It revealed that the CAGR of maize productionwas highest than rice and wheat before the green revolution i.e. 6.39 %. Still, this trend has completely reversed after adopting the green revolution, as it mainly focused on wheat and rice production. The study also reported that maize output in India had an unprecedented increase following the economic reforms of 1991 due to the adoption of single cross hybrids and ongoing demand in the domestic and export markets. Its annual growth rate is higher than that of rice and wheat.Due to its numerous uses as food and feed, its demand increased significantly in the twenty-first century.Additionally, the agricultural market reforms brought about by the APMC act of 2003, the model APMC act of 2007, and e-NAM (Electronic National Agricultural Marketing) in 2016 encouraged farmers to cultivate more maize. Also, from 2010-11 to 2020-21, the annual growth rate in MSP (Minimum Support Price) of maize is the highest than rice and wheat i.e.7%. The study noticed that, although not by 2022, maize production can soon assist farmers in increasing their income and achieving the government-set goal of doubling their income.